A Comment on Sampson (2023) - David Angenendt; Farasat Bokhari; Franco Mariusso; Junjun Zhang (Institute for Replication (I4R), 2024)
In their paper, Sampson (2023) introduces a theoretical framework and conducts empirical testing to elucidate the impact of gaps in countries' innovative efficiencies on income, wages, and trade dynamics. We successfully replicate the paper's findings by running the provided codes, and confirm the absence of any coding errors in the process. We also provide an extensive battery of robustness checks, which confirms the resilience of their results. We then scrutinize two key aspects of their study: the choice of developing countries and the innovation measure employed. The outcomes of this refined analysis partly temper the original paper's message of technology gaps driving inequality, underscoring the need for additional research in this domain.
Keywords: D31; F14; O31; O33; O47; 330